Pengaruh Penyuluhan Melalui Media Animasi Tentang Anemia Terhadap Pengetahuan dan Sikap Siswi SMAN 5 Takengon - Nababan, Agnes Sry Vera; Demitri, Athira; Yulita, Yulita; Maulizah, Nuri (Sekolah Tinggi Ilmu Kesehatan Pertamedika, 2023)
Background; anemia is a world health problem, especially in developing countries, where an estimated 30% of the world's population suffers from anemia. One of the efforts made to prevent anemia is providing counseling through animated media so that the messages conveyed are more interesting and easy to understand. Purpose; was to determine the effect of counseling through animation media about anemia on the knowledge and attitudes of female students at SMAN 5 Takengon. Method; the research method is Quasi Experimental using a one group pretest posttest design. The research was conducted at SMAN 5 Takengon from August to October 2023. The research population was 58 Class XI female students. The sampling technique used total sampling, namely 58 Class XI female students at SMAN 5 Takengon. Data analysis uses univariate analysis and bivariate analysis. Result; the majority of female students before being given counseling (Pretest) in the knowledge category, 49 female students (84.4%) had less knowledge in the attitude category, 49 female students (84.48) had less attitude, and after being given counseling (Posttest) in the category knowledge: 58 female students (100%) had good knowledge and in the attitude category, 58 female students (100%) had good attitudes. The Wilcoxon test results show that the p-value = 0.000. Conclusion; that there is an influence of education through animation media about anemia on the knowledge and attitudes of female students at SMA N 5 Takengon.